2020
DOI: 10.1097/sla.0000000000003880
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Adjuvant Cancer-specific Vaccine Therapy for Esophageal Cancer Patients Curatively Resected After Preoperative Therapy With Pathologically Positive Nodes; Possible Significance of Tumor Immune Microenvironment in its Clinical Effects

Abstract: Objectives: To elucidate the efficacy of adjuvant vaccine monotherapy using 3 Human Leukocyte Antigen (HLA)-A Ã 24-restricted tumor-specific peptide antigens for ESCC, upregulated lung cancer 10, cell division cycle associated 1, and KH domain-containing protein overexpressed in cancer 1. Summary of Background Data: ESCC patients with pathologically positive nodes (pN(þ)) have a high risk for postoperative recurrence, despite curative resection after preoperative therapy. Subclinical micrometastases are an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Although phase I and II clinical trials confirmed feasibility and safety of multi-peptide vaccination, only a small subset of patients demonstrated clinical responses [140,141]. Encouragingly, a follow-up Phase II trial, whereby patients with pathological positive lymph nodes following oesophagectomy were given an HLA-A*24:02-restricted multi-peptide vaccine, found peptide-specific cytotoxic T-cell responses, as well as improved 5-year cancer-specific survival in the vaccinated group [142]. These results have led to the investigators undertaking a subsequent large-scale, double-blind, placebo-controlled phase III trial (UMIN000016954).…”
Section: Cancer Vaccinesmentioning
confidence: 90%
See 1 more Smart Citation
“…Although phase I and II clinical trials confirmed feasibility and safety of multi-peptide vaccination, only a small subset of patients demonstrated clinical responses [140,141]. Encouragingly, a follow-up Phase II trial, whereby patients with pathological positive lymph nodes following oesophagectomy were given an HLA-A*24:02-restricted multi-peptide vaccine, found peptide-specific cytotoxic T-cell responses, as well as improved 5-year cancer-specific survival in the vaccinated group [142]. These results have led to the investigators undertaking a subsequent large-scale, double-blind, placebo-controlled phase III trial (UMIN000016954).…”
Section: Cancer Vaccinesmentioning
confidence: 90%
“…Although OAC may provide actionable tumour neoantigens, the feasibility, safety and efficacy of cancer vaccines have been mainly investigated in OSCC. In this subset of oesophageal tumours, clinical trials investigating therapeutic cancer vaccines have been undertaken utilising immunogenic TAAs [136][137][138][139][140][141][142]. Although phase I and II clinical trials confirmed feasibility and safety of multi-peptide vaccination, only a small subset of patients demonstrated clinical responses [140,141].…”
Section: Cancer Vaccinesmentioning
confidence: 99%
“…However, few biomarkers can accurately predict the prognosis of patients with ESCC (21). In addition, some studies have already demonstrated the effect of immune cells on cancers, and the immune cells in ESCC can be applied to access its therapeutic and prognostic effects (10,22). In the current study, by performing an integrated analysis of immune microenvironment and gene expression pattern, we investigated potential prognostic biomarkers in ESCC base on the following steps: (1) predict the immune cell abundance in ESCC, (2) assess the tumor microenvironment of ESCC and identify differentially expressed genes, (3) enrich DEGs through Gene Ontology and KEGG pathway analysis, (4) construct the coexpression network of immune-related DEGs through WGCNA, (5) associate immune cell infiltration and coexpression modules, ( 6) construct the survival model, and (7) validate the model and improve its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer vaccines, including peptide vaccine and dendritic cell vaccine, targeting neoantigens or shared antigens, induce and activate CTLs reactive to these antigens in cancer patients. The results of many clinical trials indicate the clinical utility of peptide vaccines targeting shared antigens derived from oncogenes specifically expressed in cancer tissues, oncoantigens [74][75][76] . In our recent phase II trial for adjuvant cancerspecific oncoantigen peptide vaccine for esophageal cancer patients who had neoadjuvant chemo(radiation)therapy and curative resection, but were found to have lymph node metastasis, patients treated with peptide vaccine showed a significantly higher 5-year esophageal cancer-specific survival rate than the non-vaccinated group (60.0% vs 32.4%, P = 0.045); the difference was more significant in patients with tumors without CD8 + or PD-L1 expression (68.0% vs 17.7%, P = 0.010) 76 .…”
Section: Personalized Immunotherapy Targeting Cancer-specific Neoantigensmentioning
confidence: 99%